2020
DOI: 10.1186/s12879-020-4833-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Vancomycin resistant enterococci (VRE) in Ethiopia: a systematic review and meta-analysis

Abstract: Background: The emergence of Vancomycin resistant enterococci (VRE) poses a major public health problem since it was first reported. Although the rising rates of VRE infections are being reported elsewhere in the worldwide; there is limited national pooled data in Ethiopia. Therefore, this study was aimed to estimate the pooled prevalence of VRE and antimicrobial resistance profiles of enterococci in Ethiopia. Methods: Literature search was done at PubMed, EMBASE, Google scholar, African Journals online (AJOL)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
6
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 59 publications
4
36
6
3
Order By: Relevance
“…Enterococcus faecalis and E. faecium are highly resistant to aminoglycosides around the world [ 12 , 68 ], including in Poland [ 14 ]. More than 50% of E. faecalis and E. faecium strains identified in Ethiopia were resistant to vancomycin, penicillin, amoxicillin, doxycycline, and tetracycline, and 60.0% of all identified enterococci were classified as MDR [ 31 ]. In the present study, enterococcus strains isolated 500 m downstream from the wastewater discharge point had similar antibiotic resistance profiles, and most of them were resistant to trimethoprim (87.5%), vancomycin, and teicoplanin (more than 75% of the strains).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Enterococcus faecalis and E. faecium are highly resistant to aminoglycosides around the world [ 12 , 68 ], including in Poland [ 14 ]. More than 50% of E. faecalis and E. faecium strains identified in Ethiopia were resistant to vancomycin, penicillin, amoxicillin, doxycycline, and tetracycline, and 60.0% of all identified enterococci were classified as MDR [ 31 ]. In the present study, enterococcus strains isolated 500 m downstream from the wastewater discharge point had similar antibiotic resistance profiles, and most of them were resistant to trimethoprim (87.5%), vancomycin, and teicoplanin (more than 75% of the strains).…”
Section: Discussionmentioning
confidence: 99%
“…However, this gene is increasingly often identified in E. faecium and E. faecalis , which suggests that it can be acquired from E. gallinarum and E. casseliflavus by horizontal transfer [ 72 ]. Multidrug-resistant enterococci and VRE have been spreading at an alarming rate in both hospitals [ 31 , 73 ] and the natural environment [ 41 , 65 ]. These pathogens could originate from various sources which have not been fully elucidated to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance development by enterococci and CoNS for different antibiotics including vancomycin is a growing challenge globally [ 3 , 17 19 ]. Vancomycin resistance for CoNS and enterococci were reported immediately after vancomycin was discovered [ 4 , 5 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia, Melese et al estimated the prevalence rate to be 14.8% (95% CI: 8.7-24.3) while in Nigeria, Wada et al estimated the prevalence of VRE from 19 original investigations to be 25.3% (95% CI: 19.8-30.8%) Acinetobacter baumannii resistance to antibiotics was also reported by many previous investigations which showed that the prevalence rate of this resistance was hugely variable according to the applied antibiotic per country. 19,20 Pormohammad et al analyzed the results of 150 original investigations in a single meta-analysis to estimate the prevalence rate of cefotaxime and colistin by country. 21 Africa had a 99% prevalence resistance rate to cefotaxime which was the highest while countries in the Western Pacific had the lowest prevalence rate of 1.1%.…”
Section: Chances Of Antibiotic Resistance (Prevalence and Associatedmentioning
confidence: 99%